Folic Acid Supplementation Does Not Prevent Ribavirin-Induced Anemia - González, Henry; Ríos, María E.; Torres, Esther A.; Muñoz, Humberto; Arroyo, Javier; Castro, Fernando J. (Puerto Rico Health Sciences Journal, 2011)
see manuscript